2021
DOI: 10.3389/fpsyg.2021.663728
|View full text |Cite
|
Sign up to set email alerts
|

A Probe Into the Psychological Mechanism of Generation Z College Students Using Network Buzzwords in the Internet Era

Abstract: Network buzzwords are ubiquitous in the internet era. To explore the psychology of college students using network buzzwords, the development trend and characteristics of network buzzwords are analyzed first. A questionnaire survey is performed to learn how college students use network buzzwords currently; then, the obtained data are analyzed and discussed. Results demonstrate that 81.59% of college students can understand what the buzzwords mean. As for psychological factors, the average score of the identity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The usage of profanity words that were initially harsh and then transformed into more neutral words, while still being used to express negative emotions, reflects this process of semantic refinement. Furthermore, a study suggests that Generation Z uses more neutral words to showcase their identity as a distinction from previous generations (Dong, 2021) The theory of social identity explains that an individual's self-image refers to the social categories they consider themselves a part of (Tajfel & Turner, 2004). This theory is reinforced by the perspective of a linguist, Steven Pinker, in his book titled "The Stuff of Thought" (Pinker, 2011).…”
Section: Theme 1: Semantic Generalizationmentioning
confidence: 99%
“…The usage of profanity words that were initially harsh and then transformed into more neutral words, while still being used to express negative emotions, reflects this process of semantic refinement. Furthermore, a study suggests that Generation Z uses more neutral words to showcase their identity as a distinction from previous generations (Dong, 2021) The theory of social identity explains that an individual's self-image refers to the social categories they consider themselves a part of (Tajfel & Turner, 2004). This theory is reinforced by the perspective of a linguist, Steven Pinker, in his book titled "The Stuff of Thought" (Pinker, 2011).…”
Section: Theme 1: Semantic Generalizationmentioning
confidence: 99%
“…When people use it, there are also problems of lack of rationality and careful thinking, such as "unclear meaning," "illogical," etc. Dong (2021) and others once believed that negative buzzwords might destroy the thinking of young people and seriously affect their life, work, and study. However, this study found that even positive Internet language, long-term use will have a certain degree of impact on people's thinking and language habits, which will be discussed in the practical significance section.…”
Section: Theoretical Findingsmentioning
confidence: 99%
“…Scholars have paid attention to these Internet buzzwords from different perspectives in terms of their characteristics, causes, and effects (Dong, 2021;Squires, 2010). However, as far as we can see,…”
Section: Introductionmentioning
confidence: 99%
“…Besides, there is not enough curriculum related to film and television education for college students and there is a lack of research literature on short video communication education. The number of publications has increased from 1 to 145 on short video communication education in China in the past 30 years, which shows that the current number is not considerable (Dong, 2021). Research on a contents-pushing algorithm by virtual image shows that the algorithm is not intelligent enough.…”
Section: Related Studiesmentioning
confidence: 99%